Career Development and Employee Retention: Addressing Brain Drain in Nepal - Silal, Jyoti (Brixton Scholarly Review, 2026)
Another challenge facing Nepal is brain drain, especially among skilled and professional groups, which negatively impacts organizational and HRD building. Although most research deals with economic push and pull factors, little research explores how internal HR practices affect brain drain intention among employees. This study aims to examine whether opportunities for career development, such as training quality, mentoring support, and clarity in promotion opportunities, reduce brain drain intention among skilled and professional groups in Nepal. The study also tests whether job satisfaction and affective commitment act as mediating factors in this relationship and whether perceived foreign opportunities reduce these relationships. A quantitative explanatory research design was used for this study. Primary data was collected from 300 skilled and professional groups in banking, ICT, healthcare, higher education, and manufacturing industries. The analysis was conducted using descriptive statistics, correlations, regression analysis, and bootstrapped mediation and moderation tests. The results indicated that good opportunities for career development enhance job satisfaction and affective commitment. These two factors reduce the intention to migrate abroad. However, attractive foreign job opportunities reduce this protective effect. The study concludes that brain drain intention in organizations can be reduced through the establishment of transparent promotion systems, mentoring, and skill-oriented training.